Estimation of ribosomal RNA transcription rate in situ - Chunhua Cui; Hung Tseng (BioTechniques)
Traditionally, the rate of transcription is measured by metabolic labeling (e.g., the run-on assay), which can be carried out only in isolated or cultured cells. It has been difficult if not impossible to assess the rate of transcription of a gene in a specific cell type in situ. We show here that the quantity of 47S precursor ribosomal RNA (pre-rRNA), which correlates positively with the rate of rRNA transcription as measured by the run-on assay, can serve as an indicator for the rate of its transcription. We adopted this method as an in situ hybridization procedure to demonstrate its validity in vivo. The notion of using the quantity of the primary transcript as an indicator of the rate of transcription has the potential application in monitoring the rate of messenger RNA transcription in single cells within a tissue of complex cellular composition.